2017
DOI: 10.1111/jphd.12212
|View full text |Cite
|
Sign up to set email alerts
|

A Markov model assessing the impact on primary care practice revenues and patient's health when using mid‐level providers, lesson learned from the United Kingdom

Abstract: In a time of limited funds for dental services, these results suggest that resources in public funded systems could be saved using mid-level providers in dental practices, without any health risk to patients or capital investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…One example is cost effectiveness. A recent simulation study from the United Kingdom found that mid‐level dental providers working in a public dental care delivery system can be a dominant strategy over dentists (i.e., improved outcomes at a lower cost) . These findings may be applicable to the YK communities.…”
Section: Discussionmentioning
confidence: 95%
“…One example is cost effectiveness. A recent simulation study from the United Kingdom found that mid‐level dental providers working in a public dental care delivery system can be a dominant strategy over dentists (i.e., improved outcomes at a lower cost) . These findings may be applicable to the YK communities.…”
Section: Discussionmentioning
confidence: 95%
“…Studies that have measured patient satisfaction with the provision of primary care have found that patients who received care from NPHWs were equally or more satisfied than those who received care from physicians [ [23] , [24] , [25] , [26] ]. In Chhattisgarh India, patients of Medical Officers and NPHWs reported similar levels of satisfaction, trust, and perceived quality, with scores of 84% for Medical Officers, 80% for AYUSH Medical Officers, and 85% for RMAs [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in Germany [22,27,2931,3437,40,42], followed by studies that were performed in the USA [18,20,25,28,32,41], in Australia [23,24,26,33,38], in the UK [19,39] and in Sweden [21]. The target populations were mainly school age children [18,21,22,28,34,35,37,41], pre-school aged children [20,25,33] and other specific populations [19,23,24,2733,36,39,40,42]. Investigated strategies included preventive intervention [25,26,32,33,41,42], screening strategy [35,36], and invasive/non-invasive treatment [1824,2731,34,37,40].…”
Section: Resultsmentioning
confidence: 99%
“…The perspectives included mixed public-private payer [27,2931,3436,40], private dental practitioner [21,23,24,38,39], public payer [18,20,26,37,41] and societal perspectives [33]. The most common modeling techniques were the Markov model [1820,24,26,28,31,33,38,39,41,42], followed by the Markov/microsimulation mixed model [27,29,30,34,35,37,40], systematic dynamic model [22,25,32], microsimulation model [23,36] and decision tree [21]. Time horizons ranged between 3.5 to 63.5 years when a life time horizon was not deployed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation